2001
DOI: 10.1152/jappl.2001.90.5.1900
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and skeletal muscle adaptations to voluntary wheel running in the mouse

Abstract: In this paper, we describe the effects of voluntary cage wheel exercise on mouse cardiac and skeletal muscle. Inbred male C57/Bl6 mice (age 6-8 wk; n = 12) [corrected] ran an average of 4.3 h/24 h, for an average distance of 6.8 km/24 h, and at an average speed of 26.4 m/min. A significant increase in the ratio of heart mass to body mass (mg/g) was evident after 2 wk of voluntary exercise, and cardiac atrial natriuretic factor and brain natriuretic peptide mRNA levels were significantly increased in the ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

49
309
11
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(372 citation statements)
references
References 45 publications
49
309
11
3
Order By: Relevance
“…In the present study, ventricular weights increased more than previously reported in mice and about the same as in rats exercising for 7 wk with the same regimen (42). Other studies in mice report no change (31) or an increase between 10 and 15% in cardiac mass (1,24), after 4 wk of training in C57BL/6J mice, treadmill, voluntary wheel, and swimming exercise, respectively. These studies lack a rigorous control of exercise intensity, and cardiovascular load seemed lower.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In the present study, ventricular weights increased more than previously reported in mice and about the same as in rats exercising for 7 wk with the same regimen (42). Other studies in mice report no change (31) or an increase between 10 and 15% in cardiac mass (1,24), after 4 wk of training in C57BL/6J mice, treadmill, voluntary wheel, and swimming exercise, respectively. These studies lack a rigorous control of exercise intensity, and cardiovascular load seemed lower.…”
Section: Discussionsupporting
confidence: 68%
“…Males had larger extensor digitorum longus muscles, but soleus muscle weight was similar. Other studies report varying results: 20-24% increased (39) and unchanged (1,19) skeletal muscle mass, and increased cross-sectional area (19,33) and GATA-2 expression (hypertrophy marker), after 4-12 wk of training (19,33). Interestingly, skeletal muscle growth occurs in mice in response to endurance training, contrary to observations in humans (4).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ces observations ont été confirmées très récem-ment par un autre groupe qui montre, en outre, que la surexpression musculaire de PPARδ confère une protection très efficace contre les effets néfastes des régimes riches en lipides, comme l'obé-sité et la résistance à l'insuline, et augmente la résistance à la fatigue musculaire [5]. Ainsi, les animaux qui surexpriment PPARδ dans leurs muscles acquiè-rent un phénotype musculaire et méta-bolique similaire au phénotype « marathonien » induit par l'entraînement d'endurance de longue durée [6]. Cela est tout à fait inattendu, puisque ces animaux ont une activité physique qui n'est pas perturbée.…”
unclassified